2019
DOI: 10.4018/978-1-5225-7068-4.ch007
|View full text |Cite
|
Sign up to set email alerts
|

Gender and Use of E-Government Services in Turkey

Abstract: This chapter investigates the relationship between gender and use of e-government services in Turkey. Based on household surveys, probit regression models are estimated to quantify determinants of e-government use for Turkish citizens. Empirical findings imply that there is a gender gap in use of e-government services. Turkish females are less likely to employ e-government tools compared to Turkish males. Household income, education level, being employed, and frequency of internet use are positively correlated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…Over the years, e-government adoption research has used the technology adoption theories or models, as its fundamental to understand citizens' behavior toward the adoption of e-government and its related applications around the globe. Some of these recent studies based on specific countries are Rufín, Bélanger, Molina, Carter, and Figueroa (2018; Spain and the United States); Maestre, Astudillo, Concha, and Nieto (2018;Colombia), Verkijika and De Wet (2018; sub-Saharan Africa); Jung (2019;Gambia); Mansoori, Sarabdeen, and Tchantchane (2018;Emirates); Abdullah, Naser, and Fayez (2018;Kuwait); Meacham, Rath, Moharana, Phalp, and Park (2019;Korea); and Kose (2019;Turkey). These adoption studies are an indication of the culture or country-specific nature of e-government services and the factors determining its adoption.…”
Section: E-government Adoptionmentioning
confidence: 99%
“…Over the years, e-government adoption research has used the technology adoption theories or models, as its fundamental to understand citizens' behavior toward the adoption of e-government and its related applications around the globe. Some of these recent studies based on specific countries are Rufín, Bélanger, Molina, Carter, and Figueroa (2018; Spain and the United States); Maestre, Astudillo, Concha, and Nieto (2018;Colombia), Verkijika and De Wet (2018; sub-Saharan Africa); Jung (2019;Gambia); Mansoori, Sarabdeen, and Tchantchane (2018;Emirates); Abdullah, Naser, and Fayez (2018;Kuwait); Meacham, Rath, Moharana, Phalp, and Park (2019;Korea); and Kose (2019;Turkey). These adoption studies are an indication of the culture or country-specific nature of e-government services and the factors determining its adoption.…”
Section: E-government Adoptionmentioning
confidence: 99%
“…But for Mensah and Mi (2019), the age and educational level variables are not viewed as decisive. Household income, employment, and the status of the respondent's residence: Szopi nski and Staniewski (2017) and Kose (2019) find significant correlations between these factors and a preference for using certain forms of eGov services. Digital skills and connectivity: Information/navigation skills and mobile skills are particularly significant (Ebbers et al, 2016).…”
Section: Digital Interaction Between Citizens and Public Administrati...mentioning
confidence: 99%
“…Kose (2019) also identifies age as being negatively correlated with the use of online government services in Turkey: as the age of the individual increases, the probability of using eGov platforms decreases. But for Mensah and Mi (2019), the age and educational level variables are not viewed as decisive. Household income, employment, and the status of the respondent’s residence: Szopiński and Staniewski (2017) and Kose (2019) find significant correlations between these factors and a preference for using certain forms of eGov services. Digital skills and connectivity: Information/navigation skills and mobile skills are particularly significant (Ebbers et al , 2016). The lack of connectivity (bandwidth limitations) is also a parameter limiting eGov use (Rana et al , 2012).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…In Ghana, a developing country in Africa, Mensah and Mi's (2018b) study confirmed the direct impact of education, age, and gender on e-government services' adoption. Kose (2019) conducted a study in Turkey and found that household income, education level, and frequency of internet use were positively correlated with the probability of e-government use by Turkish citizens. However, age showed a negative relationship with e-government use.…”
Section: E-voting Adoption and The Digital Dividementioning
confidence: 99%